Food tree species selection for nutrition‐sensitive forest landscape restoration in Burkina Faso. Issue 6 (11th August 2022) - Vinceti, Barbara; Fremout, Tobias; Termote, Celine; Fallas Conejo, Diego; Thomas, Evert; Lachat, Carl; Toe, Laeticia Celine; Thiombiano, Adjima; Zerbo, Issouf; Lompo, Djingdia; Sanou, Lassina; Parkouda, Charles; et al.
Abstract : Societal Impact Statement: Modern food systems push agriculture to focus on a small number of commercial crops, while there is a very large diversity of untapped edible plants that could be used to address food security and nutrition. Poor and monotonous diets are closely linked to the complex burden of multiple forms of malnutrition and dietary risk. In some contexts, such as West Africa, micronutrient deficiency risks are particularly pronounced. Hence, there is an urgent need to provide people with healthy diets supported by sustainable food systems. Within this context, using nutrition‐sensitive forest landscape restoration to combat environmental degradation could contribute towards ensuring the year‐round availability of nutritious tree‐based food. Summary: Diverse diets are important to deliver adequate amounts of the nutrients essential to human health. The consumption of a diversity of food groups is challenging in sub‐Saharan Africa. Trees play an important role in the direct provision of nutritious food items. Forest landscape restoration presents an opportunity to reverse the loss of useful trees, due to degradation, and increase representation of food tree species in the landscape. Here we focused on characterizing the contributions that different food products from trees can make to improving diet diversity in Burkina Faso. A scoring system was developed, based on seasonal availability of edible products and food groups covered, and was integrated into a freely available decision‐making tool that enables carrying out context‐specific, optimal choices of tree species to be considered in forest landscape restoration. Our inventory included 56 food tree species, largely Fabaceae (18 species), providing 81 edible products, mainly fruits (supplied by 79% of tree species), followed by seeds (52%) and leaves (41%). The main food groups represented are 'Other fruits' (other than vitamin A‐rich fruits) (covering 52% of the edible products) and dark‐green leafy vegetables (29%). About two thirds of the species listed produce more than a single edible product, a few up to four. A total of 11 species supplied edible products throughout the year. Our results clearly show that seasonal scarcity of food and nutrients in Burkina Faso can be partly mitigated by consuming edible tree products. The methodology can be easily scaled to other geographies. Abstract : Modern food systems push agriculture to focus on a small number of commercial crops, while there is a very large diversity of untapped edible plants that could be used to address food security and nutrition. Poor and monotonous diets are closely linked to the complex burden of multiple forms of malnutrition and dietary risk. In some contexts, such as West Africa, micronutrient deficiency risks are particularly pronounced. Hence, there is an urgent need to provide people with healthy diets supported by sustainable food systems. Within this context, using nutrition‐sensitive forest landscape restoration to combat environmental degradation could contribute towards ensuring the year‐round availability of nutritious tree‐based food. Abstract : Les systèmes alimentaires modernes se fondent sur un nombre très limité de cultures commerciales, alors qu'une très grande diversité de plantes comestibles inexploitées pourrait assurer la sécurité alimentaire et la nutrition. Les régimes alimentaires appauvris et peu diversifiés sont étroitement liés aux multiples formes de malnutrition et aux risques alimentaires. Dans certains contextes, comme en Afrique de l'Ouest, les défaillances en micronutriments sont particulièrement prononcées. Par conséquent, il urge de développer des régimes alimentaires sains, soutenus par des systèmes alimentaires durables. Dans ce contexte, la restauration des paysages forestiers pour lutter contre la dégradation de l'environnement qui s'inscrit dans une approche sensible à la nutrition pourrait contribuer à assurer la disponibilité tout au long de l'année d'aliments nutritifs dérivés des arbres.